The sinner. The complete series [videorecording (DVD)] - Biel, Jessica, 1982-; Pullman, Bill; Hecht, Jessica, 1965-; Abbott, Christopher, 1986-; Norwood, Dohn; Miller, Abby (Actress); Henig, Elisha; Coon, Carrie, 1981-; Gross, Hannah, 1990-; Paul, Natalie (Actor); Letts, Tracy, 1965-; Bomer, Matthew, 1977-; et al. (Universal Pictures Home Entertainment, 2022)
Season 1: Detective Harry Ambrose delves into the past of unassuming housewife Cora Tannetti to determine why she violently stabbed a beachgoer to death in Upstate New York.